PREDIKSI POLA PERSEBARAN TUMPAHAN MINYAK MENGGUNAKAN DATA CITRA SATELIT SENTINEL-1 DI PERAIRAN BINTAN, KEPULAUAN RIAU - Tirsa Aulia Puspitasari; Mochamad Arif Zainul Fuad; Ety Parwati (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2020)
Bintan is one of the regions with annual cases of oil spills, which were excluded from tank cleaning and black waste disposal activities. In arranging oil spill response, it is important to know the areas that are potentially affected, using oil spill trajectory model by GNOME. SAR (Sentinel-1) data is used to create coordinates for oil spills location in GNOME. SAR data processing is using SNAP software, with Lee Algorithm filter (window 5x5). The areas that potentially exposed to oil spills are known based on Environmental Sensitivity Index (ESI). In this model, oil spill will reach the Bintan Coast within 2 to 5 days with average surface current speed of 4.28 m/s (West Monsoon). The estimated of oil total amount is 1,767 barrel, which 1,157 barrel polluted the coast, 606 barrel has evaporation and dispersion and the other 4 barrel was off map. The most sensitive area to oil spills are Trily Resort Center Bintan and Sebong Bay (Index 10D). The ESI average among the Bintan region are Index 3A and 3B such as Lagoi, Tanjung Berakit, Pulau Pangkil, Pulau Mapur, Cabana, Pulau Lobam, Pantai Mayang Sari, Pantai Indah Club Med Bintan, Bintan Lagoon Resort, Pantai Senggiling, and Pengudang.